Policy Recommendations for Enhancing Sustainable Performance in Banking Through Leveraging FinTech - Mercurius Broto Legowo; Raka Fahlevi; Fangky A. Sorongan; Nguyễn Kim Thanh (Journal of Business, Finance, and Banking, 2026)
The emergence and acceleration of technology innovation and digitalization in the financial system are increasingly being developed nowadays, especially in the banking and financial sectors. One of them is financial technology, known as FinTech, which increased sustainable business performance in banking. However, it turns out that this synergy and collaboration between banking and fintech has given rise to new problems in the banking and financial system for financial and banking regulators, especially regulatory issues and their implementation. The objective of this study is to formulate policy recommendations for strategies that enhance sustainable performance in the banking sector through leveraging financial technology. For developing policy recommendations, this study uses a mixed-method research approach, which can provide credible research results. The final empirical research results developed a strategic map to inform policy recommendations for sustainable performance improvement strategies in the banking sector for leveraging FinTech. The novelty of this study lies in its application of a mixed-methods approach to formulate policy recommendations for leveraging fintech in enhancing sustainable banking performance. The findings of this study make a significant contribution to the formulation of policy recommendations for Indonesia’s financial regulators, namely Bank Indonesia and the Financial Services Authority.